2018
DOI: 10.1074/jbc.ra118.003387
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 regulates enhancer-associated H3K4 monomethylation through interactions with the methyltransferase MLL4

Abstract: Monomethylation of histone H3 lysine 4 (H3K4me1) is enriched at enhancers that are primed for activation and the levels of this histone mark are frequently altered in various human cancers. Yet, how alterations in H3K4me1 are established and the consequences of these epigenetic changes in tumorigenesis are not well understood. Using ChIP-Seq in human colon cancer cells, we demonstrate that mutant p53 depletion results in decreased H3K4me1 levels at active enhancers that reveal a striking colocalization of muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
(63 reference statements)
2
28
2
Order By: Relevance
“…Mutp53 also binds to several chromatin regulatory genes to upregulate their expression, including histone lysine methyltransferase genes MLL1 and MLL2 and histone lysine acetyltransferase gene MOZ, which in turn results in genome-wide increases of histone methylation and acetylation to regulate gene expression ( Zhu et al., 2015 ). Furthermore, mutp53 can regulate genome-wide gene expression through directly interacting with the histone lysine methyltransferase protein MLL4 ( Rahnamoun et al., 2018 ) or inducing chromatin remodeling via the interaction with the SWI/SNF chromatin-remodeling complex ( Pfister et al., 2015 ) and Pontin, the AAA+ ATPase that is associated with several chromatin-remodeling complexes (e.g. Ino80, TIP60/NuA4, and SWR1 complexes) and involved in chromatin remodeling ( Zhao et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutp53 also binds to several chromatin regulatory genes to upregulate their expression, including histone lysine methyltransferase genes MLL1 and MLL2 and histone lysine acetyltransferase gene MOZ, which in turn results in genome-wide increases of histone methylation and acetylation to regulate gene expression ( Zhu et al., 2015 ). Furthermore, mutp53 can regulate genome-wide gene expression through directly interacting with the histone lysine methyltransferase protein MLL4 ( Rahnamoun et al., 2018 ) or inducing chromatin remodeling via the interaction with the SWI/SNF chromatin-remodeling complex ( Pfister et al., 2015 ) and Pontin, the AAA+ ATPase that is associated with several chromatin-remodeling complexes (e.g. Ino80, TIP60/NuA4, and SWR1 complexes) and involved in chromatin remodeling ( Zhao et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…H3K4me2 is necessary for genomic localization of FoxA1, a pioneer factor for the androgen receptor (AR) and the estrogen receptor (ER) (Lupien et al, 2008) and, is a distinguishing epigenetic mark at cell-type-specific enhancers (Pekowska et al, 2010;Wang et al, 2014). However, recent studies challenge the canonical view of H3K4 methylation at enhancers by showing that enhancer methylation mediated by MLL3 and MLL4 is dispensable for gene regulation and development (Dhar et al, 2018;Jang et al, 2019;Rahnamoun et al, 2018). Thus, the role of different H3K4-methyl states and their regulation at enhancers is complex and remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 10 hub genes were identified using CytoHubba with a high level of connectivity - TP53 ( p53 ), KMT2B ( MLL4 ), KMT2D, EP400 ( p400 ), HDAC7, RAB2A, PIK3CD ( PI3K ), MED12 ( OPA1 ), HUWE1, and RHEB ( mTORC1 ). In the context of cellular immunity and apoptosis, Rahnamoun et al [49] reported a novel mechanism in which the mutant TP53 and KMT2B cooperated to regulate aberrant enhancer activity and tumor-promoting gene expression in response to chronic immune signaling. The EP400 E1A-associated protein, which mediates H2A.Z incorporation at specific promoters, plays a major role in cell fate decisions; it promotes cell cycle progression and inhibits apoptosis or senescence [50].…”
Section: Discussionmentioning
confidence: 99%